Canine Distemper Virus DNA Vaccination Induces Humoral and Cellular Immunity and Protects against a Lethal Intracerebral Challenge - Sixt, Nathalie (American Society for Microbiology, 1998)
We have studied the immune responses to the two glycoproteins of the Morbillivirus canine distemper virus (CDV) after DNA vaccination of BALB/c mice. The plasmids coding for both CDV hemagglutinin (H) and fusion protein (F) induce high levels of antibodies which persist for more than 6 months. Intramuscular inoculation of the CDV DNA induces a predominantly immunoglobulin G2a (IgG2a) response (Th1 response), whereas gene gun immunization with CDV H evokes exclusively an IgG1 response (Th2 response). In contrast, the CDV F gene elicited a mixed, IgG1 and IgG2a response. Mice vaccinated (by gene gun) with either the CDV H or F DNA showed a class I-restricted cytotoxic lymphocyte response. Immunized mice challenged intracerebrally with a lethal dose of a neurovirulent strain of CDV were protected. However, approximately 30% of the mice vaccinated with the CDV F DNA became obese in the first 2 months following the challenge. This was not correlated with the serum antibody levels.